Trypanosoma cruzi DNA Identification in Breast Milk from Mexican Women with Chagas Disease - María del Pilar Crisóstomo-Vázquez; Griselda Rodríguez-Martínez; Verónica Jiménez-Rojas; Leticia Eligio-García; Alfonso Reyes-López; María Hernández-Ramírez; Francisco Hernández-Juárez; José Luis Romero-Zamora; Silvia Guadalupe Vivanco-Tellez; Fortino Solorzano-Santos; Victor M. Luna-Pineda; Guillermina Campos-Valdez (Microorganisms)
(1) Background: Chagas disease is a public health problem affecting nearly 2 million women of reproductive age in Latin America. From these, 4–8% can transmit the infection to the foetus through the vertical route, whereas horizontal transmission through milk during breastfeeding remains controversial. Therefore, the presence of Trypanosoma cruzi (T. cruzi) DNA in the milk of women seropositive for Chagas disease was analysed to determine whether a relationship with the infection of their children can exist. (2) Methods: 260 pairs (mother–child) from four hospitals located in rural areas endemic to T. cruzi (state of Oaxaca) were studied. The presence of anti-T. cruzi antibodies in the serum of lactating women were determined by ELISA, whereas parasitic DNA in either breast milk or newborn’s blood was identified by PCR; (3) Results: The seroprevalence of infection in lactating women was 5.76%, and the frequency of infection detected by PCR in breast milk was 1.92%, while the frequency of infection in the blood of newborns was 1.92%. Pochutla-Oaxaca presented the highest number of positive cases in both breast milk and blood. The only risk factor found was the presence of the vector in the geographical area analysed, favouring the parasite’s transmission. Overall, the results suggest a probable transmission of T. cruzi, although whether it was through breastfeeding or through the blood during delivery could not be determined. (4) Conclusions: T. cruzi DNA was identified in lactating women’s milk and newborn blood, which is probable evidence of transmission through breastfeeding; nevertheless, future studies must be performed to confirm the presence of the parasite, alive or dead.